A method for calculating gas hydrate saturation by dual parameters of logging - Li, Haiyan; Liu, Jundong; Qu, Cuixia; Song, Hongye; Zhuang, Xueliang (Frontiers in Earth Science, 2022)
Natural gas hydrates, which only occur in geological environments with special conditions, are characterized by physical properties unique from those of oil and gas, rendering current methods of measuring saturation, such as the conventional Archie formula or the sonic velocity method, inaccurate. Therefore, to obtain a reliable saturation value of natural gas hydrates, we propose a two-parameter calculation model of resistivity and acoustic interval transit time based on logging data. The saturation results calculated using the two-parameter calculation model were far more accurate than those of the core experiment results, with the proposed model having an average relative error of 7%, whereas that of the conventional Archie formula was 24%. These results indicate that the logging two-parameter model effectively improves the calculation accuracy of gas hydrate saturation. The saturation calculation model is based on objective theory and has wide adaptability, which provides a reliable foundation for future hydrate resource evaluation, exploration, and development in the study area.